MEMAHAMI INTERNAL RATE OF RETURN (IRR): PENERAPAN PADA PEMBELAJARAN EKONOMI UNTUK MURID SMK - Faridhiya, Naufal Reza; Arif, Audry Yunus; Alwafi, Muhammad Rayhan; Ernandi, Titan Dani; Maulana, Aqsal Fikrillah; Pramana, Ferdika Yudha; Dewanto, Bimo Bayu; Gunasti, Amri; Adi, Agung Septa (Jurnal Abdi Insani, 2024)
Internal Rate of Return (IRR) is a widely used method in investment analysis to assess the feasibility and potential returns on a project. IRR is the discount rate at which the net present value (NPV) of all cash flows generated by the project becomes zero. Students of Vocational High School (SMK) Negeri 1 Jember can analyze whether a project is profitable or not with the Internal Rate of Return (IRR) analysis. This community service activity begins with observation and coordination, the next steps in sequence are the preparation of materials and tools, guidance and counseling on IRR, Simulation of IRR Application, and Evaluation of the success of the program is carried out by giving a pretest-posttest. After all the activities were carried out, a reassessment was carried out. The average score obtained was 83.75. This value increased very significantly when compared to before the implementation of the activity the average was 13.75. The implementation of this community service activity has successfully completed all the steps of the service. The evaluation results showed that all participants who took part in the training had improved their abilities with an average score of 70.